1987
DOI: 10.1017/s0003356100018833
|View full text |Cite
|
Sign up to set email alerts
|

Breed and sex differences in equally mature sheep and goats 1. Growth and food intake

Abstract: Genetic size-scaling accounts for most of the variation found among mammalian species in food intake and growth rate, with food conversion efficiency independent of the body size of the species. Is the same true of breeds and strains within species?Animals from Soay, Welsh Mountain, Southdown, Finish Landrace, Jacob, Wiltshire Horn and Oxford Down sheep breeds and from a breed of feral goats were grown to 0·40, 0·52, 0·64 or 0·76 of the mean mature weight of their breed and sex. Food was offered ad libitum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
8
21
1
Order By: Relevance
“…This observed relationship between growth rate and mature size was as expected from theoretical considerations about scaling to size (e.g. Thonney et al, 1987a;Emmans, 1988) and has been previously observed in a wide range of sheep breeds (Mason, 1967;McClelland et al, 1976). In contrast, Zervas et al (1977) and Matsoukas et al (1987) found no significant difference in growth rates between Serres and Karagouniko sheep.…”
Section: Growth and Potential Growthsupporting
confidence: 88%
“…This observed relationship between growth rate and mature size was as expected from theoretical considerations about scaling to size (e.g. Thonney et al, 1987a;Emmans, 1988) and has been previously observed in a wide range of sheep breeds (Mason, 1967;McClelland et al, 1976). In contrast, Zervas et al (1977) and Matsoukas et al (1987) found no significant difference in growth rates between Serres and Karagouniko sheep.…”
Section: Growth and Potential Growthsupporting
confidence: 88%
“…These values are marginally higher than those reported by Thonney et al (1987a;04 to 0-52 maturity interval) of 177 and 200 g/day for females and males respectively. These values are marginally higher than those reported by Thonney et al (1987a;04 to 0-52 maturity interval) of 177 and 200 g/day for females and males respectively.…”
Section: Welsh Mountaincontrasting
confidence: 65%
“…0-03)) ( Table 3). Comparison of this b value for total muscle with those given by Thonney et al (1987a) for shorn, fasted slaughter weight (b = 1-02 (s.e. 0-03)) and for shorn empty body weight (b = 1-05 (s.e.…”
Section: Allometric Growthmentioning
confidence: 96%
“…Maturity x sex, maturity x breed and sex x breed interactions also were included. The method of analysis is described in Thonney et al (1987a).…”
Section: Analysis Of Datamentioning
confidence: 99%